Nonperforming loans in Asia determinants and macrofinancial linkages. - Lee, Junkyu; Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
The empirical study demonstrates that while macroeconomic conditions and bank-specific factors such as weak gross domestic product growth and rapid credit growth contribute to the buildup of nonperforming loans, a sustained increase of nonperforming loans can also lead to a reduction in credit supply and slowdown in overall economic activity. These findings underline the importance of considering policy options to swiftly and effectively manage and respond to a buildup of nonperforming loans.
Keywords: Financial institutions; Finance -- Asia; Asian Development Bank; Electronic book